APPLICATION OF THE KAIZEN 5S METHOD FOR THE LAYOUT OF THE WAREHOUSE SECTION - Ali Mukhtar, M. Nushron; Muhajir, M. Asy’aril (UNIPA PRESS, 2020)
Warehouse as a place that is burdenedwith the task of and items to be used inproduction, until the goods are requestedaccording to the operating schedule. Thepurpose of this study is to find out how toplace, group, and compile items to be orderly.The average results in preparing the PO afterimplementation are proven to be faster thanbefore implementation, so Ho is rejected.Statistical test results with an average ratiothat shows the average time beforeimplementation is 16.37 and the results afterimplementation are 2.04 and it is obviouslythat after implementation there has been asignificant decrease in the service of purchaseorders (PO) more fast.